2018
DOI: 10.1039/c8ra02422g
|View full text |Cite|
|
Sign up to set email alerts
|

Patchouli oil isolated from the leaves of Pogostemon cablin ameliorates ethanol-induced acute liver injury in rats via inhibition of oxidative stress and lipid accumulation

Abstract: Excessive alcohol consumption can cause serious hepatic injury which is associated with oxidative stress and fatty metabolic disturbance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…It is frequently used for essential oils products [ 13 , 14 ]. The plant is mainly cultivated in Southeast Asia and is commercially used in perfumes and aromatherapy [ 14 , 15 ]. Patchouli essential oil (PEO) recently received much attention due to its diverse bioactivity including anti-inflammatory effects, antiviral activities, antioxidant effects, wound healing, and inhibitory effects on lipid accumulation [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is frequently used for essential oils products [ 13 , 14 ]. The plant is mainly cultivated in Southeast Asia and is commercially used in perfumes and aromatherapy [ 14 , 15 ]. Patchouli essential oil (PEO) recently received much attention due to its diverse bioactivity including anti-inflammatory effects, antiviral activities, antioxidant effects, wound healing, and inhibitory effects on lipid accumulation [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The plant is mainly cultivated in Southeast Asia and is commercially used in perfumes and aromatherapy [ 14 , 15 ]. Patchouli essential oil (PEO) recently received much attention due to its diverse bioactivity including anti-inflammatory effects, antiviral activities, antioxidant effects, wound healing, and inhibitory effects on lipid accumulation [ 15 , 16 , 17 ]. Patchouli has also been reported to suppress food intake and weight gain [ 18 ], while the major volatile compounds of PEO were characterized such as patchouli alcohol, α -patchoulene, and β -patchoulene [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, β-caryophyllene was also found to improve cisplatin-induced nephrotoxicity in a cannabinoid 2 receptor-dependent manner (Calleja et al, 2013[ 17 ]). Seychellene, α-bergamotene and valencene were found to have high antioxidant, anti-inflammatory and also anti-apoptotic properties against chemical-induced toxicity in rats (Huang et al, 2018[ 40 ]; Su et al, 2012[ 77 ]; Tsai et al, 2010[ 81 ]; Tsoyi et al, 2011[ 82 ]).…”
Section: Discussionmentioning
confidence: 99%
“…According to GC-MS analysis, the most abundant ingredient is patchouli alcohol, with a content of 34.3 %. It has been revealed that patchouli alcohol does a variety of pharmacological activities including anti-oxidation, anti-inflammatory, and antilipogenesis [11,28,29], and these activities are associated with the treatment of NAFLD. Thus, the effect of PO against NAFLD might be related to the content of patchouli alcohol in PO, and patchouli alcohol might act as the main active ingredient.…”
Section: Discussionmentioning
confidence: 99%
“…PO is the essential oil extracted from the dry leaves of Pogostemon cablin with multiple biological activities such as anti-oxidation and anti-inflammation [9,10]. In our previous study, we found that PO has obvious protective effect against hepatic lipidosis in alcoholic liver disease [11]. Itʼs indicated that PO might be able to protect the liver from hepatic steatosis.…”
Section: Introductionmentioning
confidence: 99%